Acute lymphoblastic leukemia and lymphoblastic lymphoma in adolescents and young adults. Issue 6 (8th February 2018) - McNeer, Jennifer L.; Bleyer, Archie
Abstract: Compared to younger and older age groups, the incidence of acute lymphoblastic leukemia (ALL) and lymphoblastic lymphoma (LBL) has increased more in the adolescent and young adult (AYA) population, the cause of which is unknown. As of the last decade, only half of the AYA patients with these diseases were surviving 10 years. Strong evidence exists that favors "pediatric" treatment regimens for AYAs compared to "adult" treatment regimens in terms of survival rates, hospitalization time, toxicities, late effects, and quality of life both during and after treatment. Targeted agents are clinically accessible for certain subsets of patients with Philadelphia‐like ALL, the incidence of which peaks in AYAs. Treatment teams must appreciate the complex psychosocial underpinnings in these patients in order to maximize compliance with the prolonged and complex treatment plans during the AYA years.1